EFFECT OF PESTICIDE USES ON AGRICULTURE’S HEALTH AT KUET CHANG SUB-DISTRICT, MAE TAENG DISTRICT, CHIANG MAI PROVINCE - Pasanit, Preeda (Journal of MCU Nakhondhat, 2025)
This research aimed to 1) Examine the health status of farmers who use pesticides, 2) Investigate the factors associated with their health, and 3) Explore specific factors affecting the health of farmers in Kuet Chang Sub - district, Mae Taeng District, Chiang Mai Province. This study employed a descriptive research design. Data were collected from 249 farmers aged 18 years and older using a structured questionnaire. Descriptive statistics and logistic regression analysis were used to identify factors associated with the health of farmers who use pesticides. The results of the study showed that the factors related to various symptoms in farmers who used pesticides were as follows: 1) Demographic factors: Gender was associated with neurological symptoms, education level was related to respiratory and chest symptoms and smoking history was linked to eye symptoms. Coffee consumption was associated with skin and gastrointestinal symptoms. 2) Agricultural factors: Duration of farming and work duties were associated with symptoms across multiple systems, including the respiratory, chest, and skin systems. Pesticide use and its duration were related to neurological, respiratory, and chest symptoms. Additionally, the disposal of chemical containers, sprayer type, and nozzle type were associated with skin, nervous system, and eye symptoms. The study highlights the importance of pesticide use management to reduce health risks among farmers, emphasizing the need for proper training, protective measures, and regular health monitoring.